THE GREAT ANCIENT FOODS AND FOOD PRACTICES THAT PREVENTS AILMENTS LIKE CANCER - K. S. S. Siva Krishna; P.V.N.R.Prasad; K. Sai Prasanna (International Journal of Applied Ayurved Research, 2017)
Every country has a different way of living, but more importantly they have different foods and food habits. India is known for its exotic spices since ancient times. The civilization of India goes back to the 2500B.C. and during that time even food was a major part of Indian lives. They created traditional believes meal composition and cycles special occasions such as feasting and fasting. The greatness of our ancestors is that they included all the medicinal properties consisting items in their dietary menu along with it they followed a healthy food practices which kept them far away from certain ailments. Discussed some of the foods and food practices of ancient Indians which helped them to stay far from the dreadful diseases like cancers.